PENGEMBANGAN MODEL PEMBELAJARAN MULTILITERASI PADA MATA PELAJARAN AQIDAH AKHLAK MATERI PERGAULAN REMAJA - Ade Miftahul Irfan; Hidayatullah Hidayatullah; Apud Apud (QATHRUNÂ, 2021)
This research is motivated by the monotony of learning the subjects of aqidah morality, there are still many students who have not implemented the moral aqidah subjects, especially the material for this youth association in everyday life. Aqidah morals subject matter of adolescent association has basic competencies (KD) that should be understood and applied by Madrasah students. The formulation of the problem in this study is how the development and effectiveness of the multi-literacy learning model in the subjects of aqidah morals material for adolescent relationships at MAN 2 Serang City.This study aims to develop and measure the effectiveness of the product of a multiliterate learning model on the subject of Aqidah Morals, material for adolescent relationships at MAN 2 Serang City. The method used in this research is Research and Development or development research using Borg and Gall steps which are simplified into five stages. The results showed that menunjukkanExpert validation was carried out by two experts, namely, learning design experts and material experts. Received "good" predicate. Then, during product trials in the field, the researchers conducted online, consisting of questionnaires, small-scale tests and large-scale tests. With the following results received the predicate "Good". The conclusions obtained from this research are The development of a multiliterate learning model in the subjects of Aqeedah Akhlak, material for adolescent socialization, has been successfully developed through a research procedure based on the R&D development model and refers to the research steps according to Borg and Gall which are simplified into five stages.